The Post-mating Switch in the Pheromone Response of Nasonia Females Is Mediated by Dopamine and Can Be Reversed by Appetitive Learning - Lenschow, Maria; Cordel, Michael; Pokorny, Tamara; Mair, Magdalena M.; Hofferberth, John; Ruther, Joachim (Frontiers in Behavioral Neuroscience, 2018)
The olfactory sense is of crucial importance for animals, but their response to chemical stimuli is plastic and depends on their physiological state and prior experience. In many insect species, mating status influences the response to sex pheromones, but the underlying neuromodulatory mechanisms are poorly understood. After mating, females of the parasitic wasp Nasonia vitripennis are no longer attracted to the male sex pheromone. Here we show that this post-mating behavioral switch is mediated by dopamine (DA). Females fed a DA-receptor antagonist prior to mating maintained their attraction to the male pheromone after mating while virgin females injected with DA became unresponsive. However, the switch is reversible as mated females regained their pheromone preference after appetitive learning. Feeding mated N. vitripennis females with antagonists of either octopamine- (OA) or DA-receptors prevented relearning of the pheromone preference suggesting that both receptors are involved in appetitive learning. Moreover, DA injection into mated females was sufficient to mimic the oviposition reward during odor conditioning with the male pheromone. Our data indicate that DA plays a key role in the plastic pheromone response of N. vitripennis females and reveal some striking parallels between insects and mammals in the neuromodulatory mechanisms underlying olfactory plasticity.